Computer aided feedback in technique training - Krug, J. (World Congress of Performance Analysis of Sport VIII, 2008)
There is not a generalized theoretical position for the investigation in the field of computer aided feedback in technique training (Daugs, 2000). Though, precise studies of the training effect are seldom. The range between high and low effects shows that standards are missing for the studies in this field. Standards should be: (1) definition of criteria of performance, (2) research designs with 2x2 plan and retention test, (3) evaluation of the transfer into the performance of competition, (4) protocols to the frequency of feedback and training sessions.